Does community context have important bearings on the divorce rate? A fixed-effects study of twenty Norwegian first-marriage cohorts - Torkild H. Lyngstad (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2006)
Decisions to divorce could be affected by a number of characteristics of the local community. Community characteristics may be barriers to divorce (e.g. strong social control) or increase the attractiveness of divorcing (e.g. through access to a good remarriage market), but our knowledge of such influences is sparse. This study examines the impact of several community-level factors that may influence a couple's risk of divorce: Socioeconomic conditions, the local marriage market, and the normative climate. Discrete-time hazard models with community-level fixed effects are estimated using a register-based data set of all Norwegian first marriages contracted 1980-2000 that includes longitudinal information on both the community and the couple level. Results show that higher average education, an unbalanced marriage market, and population density drive divorce rates down but that economic conditions do not matter for divorce risk. Estimates obtained from regular models are markedly different than those obtained with the fixed-effects approach.
Keywords: 300; Community; context; divorce; fixed-effects; hazard; multilevel; registers; Ehe; Gemeinschaft; Gesellschaftsordnung; Schätzung; Norwegen